2006
DOI: 10.1080/0972060x.2006.10643475
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of the Fruits ofEletteria cardamomum

Abstract: A steam distilled essential oil obtained from fruits of Eletteria cardamomum was characterized by a high proportion of monoterpenes (87.6%). The main monoterpenes was 1,8-cineole (35.6%) followed by α-terpenyl acetate (27.1%), α-terpineol (4.9%), linalool (4.1%) and thujyl alcohol.Sesquiterpenic constituents amounting to only 1.8 % were represented by t-caryophyllene (0.8 %) and valencene (1%). Other important volatile constituents identified in the oil were α-phellandrene (2.5 %), cis-ocimene (2.4 %) and nery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…(Cupressaceae), Stachys glutinosa L. (Lamiaceae), Gundelia tournifortii L. (Asteraceae), Dysphania ambrosioides (L.) Mosyakin & Clemants (syn. Chenopodium abrosioides L.) (Amaranthaceae) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. α-TA is a commercially important fragrance molecule with sweet, herbaceous floral and lavender odor.…”
Section: Introductionmentioning
confidence: 99%
“…(Cupressaceae), Stachys glutinosa L. (Lamiaceae), Gundelia tournifortii L. (Asteraceae), Dysphania ambrosioides (L.) Mosyakin & Clemants (syn. Chenopodium abrosioides L.) (Amaranthaceae) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. α-TA is a commercially important fragrance molecule with sweet, herbaceous floral and lavender odor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in the chemical composition of different species of cardamoms, monoterpenes are the main compounds [ 14 , 17 , 20 , 21 , 22 ]. Also, antimicrobial activity of the cardamoms is reported [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two sesquiterpene constituents, cardinen and nerolidol, and a phenol derivative of p-cresol were also identified (Table 2). Different chemotypes have been reported from CEO richness of 1,8-cineole, α-terpinyl acetate, α-terpineol, β-terpineol, βmyrcene, sabinene, β-linalool, α-terpinyl acetate, geranyl acetate, limonene, nerol, and linalyl acetate was reported by several workers (Miniraj et al, 2000;Murugan et al, 2002Murugan et al, , 2005Kumar et al, 2005;Kaskoos et al, 2006;Goudarzvand Chegini and Abbasipour, 2017;Alagupalamuthirsolai et al, 2019;Ashokkumar et al, 2019). To find out the similarity of oil composition among the 22 cardamom accessions, a hierarchical cluster analysis was carried out based on the composition of its major constituents (Figure 3).…”
Section: Resultsmentioning
confidence: 92%